Brazilian infant and preschool children feeding: literature review - Carolina Santos Mello; Karina Vieira Barros; Mauro Batista de Morais (Jornal de Pediatria, 2016)
Objective: To assess the feeding profile of Brazilian infants and preschool children aged 6 months to 6 years, based on the qualitative and quantitative analysis of food and nutrient intake. Data source: This review analyzed studies carried out in Brazil that had food survey data on infants and preschool children. The search was limited to publications from the last 10 years included in the LILACS and MEDLINE electronic databases. Data summary: The initial search identified 1480 articles, of which 1411 were excluded after the analysis of abstracts, as they were repeated or did not meet the inclusion criteria. Of the 69 articles assessed in full, 31 articles contained data on food survey and were selected. Only three studies concurrently assessed children from different Brazilian geographical regions. Of the assessed articles, eight had qualitative data, with descriptive analysis of food consumption frequency, and 23 had predominantly quantitative data, with information on energy and nutrient consumption. Conclusions: The articles assessed in this review showed very heterogeneous results, making it difficult to compare findings. Overall, the feeding of infants and preschool children is characterized by low consumption of meat, fruits, and vegetables; high consumption of cow's milk and inadequate preparation of bottles; as well as early and high intake of fried foods, candies/sweets, soft drinks, and salt. These results provide aid for the development of strategies that aim to achieve better quality feeding of Brazilian infants and preschoolers. Resumo: Objetivo: Verificar o perfil alimentar do lactente e do pré-escolar brasileiro, na faixa etária de 6 meses aos 6 anos, a partir da análise qualitativa e quantitativa do consumo de alimentos e nutrientes. Fontes de dados: Nesta revisão foram analisados estudos realizados no Brasil que apresentavam dados de inquéritos alimentares de lactentes e pré-escolares. A busca foi limitada às publicações dos últimos 10 anos, incluídas nas bases de dados eletrônicas Lilacs e Medline. Síntese dos dados: Na pesquisa inicial foram identificados 1480 artigos, 1411 foram excluídos após análise dos resumos, por serem repetidos ou não preencherem os critérios de inclusão. Dos 69 artigos avaliados na íntegra, foram selecionados 31 artigos que continham dados sobre alimentação. Apenas 3 trabalhos avaliaram concomitantemente crianças de diferentes regiões geográficas brasileiras. Dos artigos analisados, 8 apresentavam informações qualitativas, com análise descritiva da frequência de consumo alimentar e 23, informações predominantemente quantitativas, com dados de consumo energético e de nutrientes. Conclusões: Os artigos analisados na presente revisão apresentaram resultados bastante heterogêneos, dificultando a comparação dos achados. De um modo geral, a alimentação do lactente e do pré-escolar é caracterizada pelo baixo consumo de carnes, frutas, legumes e verduras, por elevado consumo de leite de vaca e inadequação no preparo de mamadeiras, além de precoce e elevado consumo de frituras, doces, refrigerantes e sal. Nossos resultados constituem subsídios para a elaboração de estratégias que visem melhor a qualidade da alimentação do lactente e do pré-escolar brasileiro. Keywords: Feeding, Child nutrition, Infant, Preschool child, Brazil, Palavras-chave: Alimentação, Nutrição da criança, Lactente, Pré-escolar, Brasil